Adnexal torsion without neoplastic lesions after laparoscopic hysterectomy: A report of three cases and literature review. Issue 2 (16th December 2020) - Ogawa, Chiemi; Amano, Tsukuru; Higuchi, Asuka; Tsuji, Shunichiro; Kimura, Fuminori; Murakami, Takashi
Abstract: The major risk factor for adnexal torsion is the presence of adnexal neoplasms, and torsion without a neoplastic lesion of the adnexa is rare. We report three cases of right adnexal torsion without neoplastic lesion after laparoscopic hysterectomy. In all three cases, the right adnexas, which did not form adhesions, had undergone torsion. According to several case reports, most cases of adnexal torsion after laparoscopic hysterectomy developed without neoplastic lesion. In fact, adnexal torsion without neoplasm is reported to occur relatively frequently after laparoscopic hysterectomy and more commonly involves the right side. Therefore, at the end of laparoscopic hysterectomy, ovariopexy should be performed to prevent postoperative adnexal torsion.